P675 Two recent cases of extensively drug-resistant (XDR) gonorrhoea in the united kingdom linked to a european party destination. (14th July 2019) - Horner, Paddy; Fifer, Helen; Nathan, Bavithra; Eyre, David; Town, Katy; Mohammed, Hamish; Cole, Michelle; Pitt, Rachel; Gobin, Maya; Irish, Charles; Gardiner, Daniel; Sedgwick, James; et al.
Abstract : Background: The development of antimicrobial resistance (AMR) to macrolides and extended-spectrum cephalosporins (ESC) in Neisseria gonorrhoeae (NG), is a major public health concern. While macrolide AMR is increasing globally, ESC AMR is low and extensive drug-resistance (XDR) rare. Methods: We report the clinical management and microbiology of two recent cases of XDR NG in the UK. Results: Case A (female) presented to a sexual health clinic (SHC) in October 2018 with urinary symptoms. She cleared the infection following treatment with ceftriaxone 500 mg plus azithromycin 1g. She had recently had vaginal intercourse with ≥1 male partner in Ibiza, Spain. Case B (female) presented to a SHC elsewhere in England in November 2018 with anal and genital symptoms. She had recently had unprotected vaginal, oral and anal sex with an asymptomatic man who had been in Ibiza and had links with the same sexual network as case A. He tested NG NAAT-negative in December without treatment. Case B initially responded clinically to treatment with ceftriaxone 1g, but symptoms relapsed and she remained culture-positive 2 weeks later. She failed subsequent treatment with gentamicin 240 mg plus azithromycin 2g but cleared the infection with 3 days of IV ertapenem. Both isolates were resistant to ceftriaxone (MIC 1.0 mg/L), cefixime, penicillin, ciprofloxacin and tetracycline, had intermediate susceptibility to azithromycin (MIC 0.5 mg/L), and were susceptible to spectinomycin. Whole genome sequencing indicated that both isolates were from the FC428 clone, which has been reported sporadically globally, usually with epidemiological links to the Asia-Pacific region. Conclusion: These FC428 clone isolates are able to cause both asymptomatic and symptomatic infection with a variable response to ceftriaxone and azithromycin treatment. This clone is likely to increase over time in Europe and threatens the effectiveness of gonorrhoea treatment. Surveillance of AMR, test-of-cure, extra-genital sampling and partner notification are vital to maintain effective treatment and prevent spread. Disclosure: No significant relationships.